Micro-nano-bio acoustic system for the detection of foodborne pathogens in real samples - Papadakis, George; Krulišová, Pavla; Hamiot, Audrey; Tsougeni, Katerina; Kaprou, Georgia; Eck, Michael; Rabus, David; Bílková, Zuzana; Dupuy, Bruno; Jobst, Gerhardt; Tserepi, Angeliki; Gogolides, Evangelos; et al. (My University, 2018)
The fast and efficient detection of foodborne pathogens is a societal priority, given the large number of food-poisoning outbreaks, and a scientific and technological challenge, given the need to detect as little as 1 viablecell in 25 gr of food. Here, we present thefirst approach that achieves the above goal, thanks to the use of amicro/nano-technology and the detection capability of acoustic wave sensors. Starting from 1Salmonellacell in25 ml of milk, we employ immuno-magnetic beads to capture cells after only 3 h of pre-enrichment and sub-sequently demonstrate efficient DNA amplification using the Loop Mediated Isothermal Amplification method(LAMP) and acoustic detection in an integrated platform, within an additional ½ h. The demonstrated 4 hsample-to-analysis time comes as a huge improvement to the current need of few days to obtain the same result.In addition, the work presents thefirst reported Lab-on-Chip platform that comprises an acoustic device as thesensing element, exhibiting impressive analytical features, namely, an acoustic limit of detection of 2 cells/μlor3 aM of the DNA target and ability to detect in a label-free manner dsDNA amplicons in impure samples. The useof food samples together with the incorporation of the necessary pre-enrichment step and ability for multipleanalysis with an internal control, make the proposed methodology highly relevant to real-world applications.Moreover, the work suggests that acoustic wave devices can be used as an attractive alternative to electro-chemical sensors in integrated platforms for applications in food safety and the point-of-care diagnostics.
Mikro-nano-bio akustický systém pro detekci patogenů v potravinách v reálných vzorcích
Keywords: Lab-on-chip; Molecular diagnostics; Acoustic biosenzor; Salmonella detection; Lab-on-chip; Molekulární diagnostika; akustický biosenzor; detekce Salmonelly